John Adams : In His Own Words. - Baron, Robert C. (Speaker's Corner., 2009)
John Adams-second president of the United States and one of the great figures in American history-was a remarkable, outspoken political philosopher with ideas reaching far beyond his time. This superb collection of writing and letters explores the personal side of John Adams, offering firsthand accounts and analysis of the events of his era as well as insight into the man behind the public face.